Studi Implementasi Aplikasi Keuangan Android dengan Analisis Data - Rizki Dwi Sanjaya; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
In this modern era, efficient personal financial management tools are increasingly needed. Applications for Android-based mobile phones offer an efficient and easy-to-use method of managing personal finances. The aim of this research is to create and implement a personal financial management application that has data analysis features that help people manage income, expenses and savings. The app has features such as transaction recording, financial reporting, and data analysis, which provides information on spending patterns and recommendations for reducing costs. This study uses user interface design, application development using Android Studio, and application testing with end users. Studies show that these apps can help people make better financial decisions and better understand their financial condition. This research helps develop mobile applications by including data analysis features that help users manage finances.